Bimatoprost Intracameral Implant (Durysta®): A New Era in Glaucoma Management Through Sustained-Release Innovation - Vagiakis I; Papadopoulou EP; Amaxilati E; Tsiropoulos GN; Konstas AG; Panos GD (Drug Design, Development and Therapy, 2025)
Iordanis Vagiakis,1 Eleni P Papadopoulou,1 Efstratia Amaxilati,1 Georgios N Tsiropoulos,1 Anastasios G Konstas,1,* Georgios D Panos1,2,* 1First Department of Ophthalmology, AHEPA University Hospital, School of Medicine, Aristotle University of Thessaloniki, Thessaloniki, Greece; 2Division of Ophthalmology and Visual Sciences, School of Medicine, University of Nottingham, Nottingham, UK*These authors contributed equally to this workCorrespondence: Georgios D Panos; Iordanis Vagiakis, First Department of Ophthalmology, AHEPA University Hospital, School of Medicine, Aristotle University of Thessaloniki, Kiriakidi 1, Thessaloniki, 54636, Greece, Tel +30 231 330 3110, Email gdpanos@gmail.com; jvag_@outlook.comAbstract: The bimatoprost intracameral implant (Durysta®) offers a sustained-release approach to glaucoma management, providing consistent intraocular pressure (IOP) reduction over several months and reducing the need for daily topical therapies. This review evaluates its pharmacology, efficacy, and safety, using data from pivotal clinical trials and recent real-world studies. The implant achieves IOP reductions comparable to topical prostaglandin analogs, with benefits for patient adherence and fewer common side effects. However, repeat administrations are associated with adverse effects such as endothelial cell loss, highlighting the need for optimized re-dosing schedules. Future research should explore its use in advanced glaucomas, cost-effectiveness, and combination with other IOP-lowering treatments. The bimatoprost intracameral implant represents a promising innovation in glaucoma therapy with potential for improved patient outcomes.Keywords: bimatoprost intracameral implant, glaucoma, intraocular pressure reduction, sustained-release therapy, primary open-angle glaucoma, ophthalmic drug delivery, patient adherence, prostaglandin analogs, endothelial cell safety, real-world evidence, cost-effectiveness, combination therapy in glaucoma